Slovenian Pet Owners' Experience, Attitudes, and Predictors Regarding Cannabinoid Use in Dogs and Cats - Tomsič, Katerina; Rakinić, Kristina; Seliškar, Alenka (Frontiers in Veterinary Science, 2022)
The aim of this study was to assess the personal experience and attitudes of Slovenian pet owners regarding cannabinoid (CBD) use and to identify the predictors of the first use and reuse of CBDs in dogs and cats. We hypothesized that positive attitudes toward CBDs, postmodern health values, and personal experience would be significant predictors of CBD use in animals. An open online survey targeted randomly selected Slovenian dog and cat owners, regardless of their experience with cannabis products. The questionnaire consisted of six sections related to demographic data and personal experience with CBD use, information about the participant's animal, experience with CBD use in the participant's animal, reasons for not using CBDs in their animal, attitudes toward CBD use in dogs and cats, and postmodern health values. Descriptive statistics were performed to analyze demographics, personal experience with CBD use, and experience with CBD use in dogs and cats. Hierarchical multiple regression using the enter method was performed to analyze the important predictors of CBD use. A total of 408 completed questionnaires were included in the statistical analysis. A substantial proportion (38.5%) of owners had already used CBDs to treat their animal. Positive attitudes and previous personal experience were significant (p < 0.05) predictors of first use and reuse of CBDs in pets, while postmodern health values were not. In conclusion, the decision to use CBDs for medicinal purposes is based on acquired information and personal experience. Veterinarians should be informed and familiar with CBDs as a treatment option. However, further research is essential to establish the use of CBDs in veterinary medicine. Improved laws and regulations are also needed to ensure that only high-quality medications are prescribed to dogs and cats.